Christmas mourning [large type] - Maron, Margaret (Maron, Margaret. Deborah Knott mystery., 2010)
North Carolina judge Deborah Knott and her husband Deputy Dwight Bryant are looking forward to Christmas until a traffic fatality turns out not to be an accident.